Bumetanide Prevents Brain Trauma-Induced Depressive-Like Behavior - Goubert, Emmanuelle; Altvater, Marc; Rovira, Marie-Noelle; Khalilov, Ilgam; Mazzarino, Morgane; Sebastiani, Anne; Schaefer, Michael K. E.; Rivera, Claudio; Pellegrino, Christophe (Frontiers in Molecular Neuroscience, 2019)
Brain trauma triggers a cascade of deleterious events leading to enhanced incidence of drug resistant epilepsies, depression and cognitive dysfunctions. The underlying mechanisms leading to these alterations are poorly understood and treatment that attenuates those sequels not available. Using controlled-cortical impact (CCI) as experimental model of brain trauma in adult mouse we found a strong suppressive effect of the sodium-potassium-chloride importer (NKCC1) specific antagonist bumetanide on appearance of depression-like behavior. We demonstrate that this alteration in behavior is associated with a block of CCI-induced decrease in parvalbumin-positive interneurons and impairment of post-traumatic secondary neurogenesis within the dentate gyrus of the hippocampus. The mechanism mediating the effect of bumetanide involves early transient changes in expression of chloride regulatory proteins and qualitative changes in GABA(A) mediated transmission after brain trauma. This work opens new perspectives in the early treatment of human post-traumatic induced depression. Our results strongly suggest that bumetanide might constitute an efficient prophylactic treatment to reduce neurological and psychiatric consequences of brain trauma.